P1838 Defining the Optimal Temporal and Spatial Resolution for Cardiovascular Magnetic Resonance Imaging Feature Tracking. (17th January 2020) - Backhaus, S J; Metschies, G; Billing, M; Kowallick, J T; Gertz, R J; Lapinskas, T; Pieske-Kraigher, E; Pieske, B; Bigalke, B; Kutty, S; Hasenfus, G; Kelle, S; et al.
Abstract: Background: Myocardial deformation analyses using cardiovascular magnetic resonance feature tracking (CMR-FT) have incremental value in the assessment of cardiac function beyond volumetric analyses. Since guidelines do not recommend specific imaging parameters, we aimed to define optimal spatial and temporal resolutions for CMR cine images to enable reliable post-processing. Methods: Intra- and inter-observer reproducibility was assessed in 12 healthy volunteers. Cine images were acquired with differing temporal (20, 30, 40 and 50 frames/cardiac cycle) and spatial resolutions (high in-plane 1.5x1.5mm through-plane 5mm, standard 1.8x1.8x8mm and low 3.0x3.0x10mm). CMR-FT analyses comprised left ventricular (LV) global longitudinal strain (GLS) and systolic strain rate (SRs) as well as LV circumferential and radial strains (GCS and GRS) and right ventricular (RV) GLS. Intra- and inter-observer reproducibility was assessed in all subjects. Results: Temporal but not spatial resolution did impact absolute strain and SR. Maximum absolute changes between lowest and highest temporal resolution were as follows: 2.3% LV GLS, 2.2% GCS, 7.2% GRS, 1.7% RV GLS and 0.32s-1 SRs. Changes of time-integrated (strain) values occurred predominantly comparing 20 and 30 frames/cardiac cycle including LV GLS, GCS and GRS (p = 0.034, p = 0.008 and p = 0.034) in highest spatial resolution settings. In contrast, time-derivatives values (SRs) changed significantly from lower temporal resolutions to 40 frames/cardiac cycle and beyond (20 to 30 p = 0.002; 30 to 40 p = 0.018; 40 to 50 frames/cardiac cycle p = 0.075) in highest spatial resolution settings. Strain reproducibility was not affected by either temporal or spatial resolution. SRs variability as assessed by coefficient of variation decreased with higher temporal resolutions. Conclusion: Temporal but not spatial resolutions significantly affect strain and SR in CMR-FT deformation analyses. Clinical CMR-FT strain and SR analyses require minimum temporal resolutions of 30 and 40frames/cardiac cycle, respectively to ensure precise quantification of myocardial function.